The GRADE evidence-to-decision framework: a report of its testing and application in 15 international guideline panels. (December 2015) - Neumann, Ignacio; Brignardello-Petersen, Romina; Wiercioch, Wojtek; Carrasco-Labra, Alonso; Cuello, Carlos; Akl, Elie; Mustafa, Reem; Al-Hazzani, Waleed; Etxeandia-Ikobaltzeta, Itziar; Rojas, Maria; Falavigna, Maicon; Santesso, Nancy; et al.
Abstract Background Judgments underlying guideline recommendations are seldom recorded and presented in a systematic fashion. The GRADE Evidence-to-Decision Framework (EtD) offers a transparent way to record and report guideline developers' judgments. In this paper, we report the experiences with the EtD frameworks in 15 real guideline panels. Methods Following the guideline panel meetings, we asked methodologists participating in the panel to provide feedback regarding the EtD framework. They were instructed to consider their own experience and the feedback collected from the rest of the panel. Two investigators independently summarized the responses and jointly interpreted the data using pre-specified domains as coding system. We asked methodologists to review the results and provide further input to improve the structure of the EtDs iteratively. Results The EtD framework was well received, and the comments were generally positive. Methodologists felt that in a real guideline panel, the EtD framework helps structuring a complex process through relatively simple steps in an explicit and transparent way. However, some sections (e.g., "values and preferences" and "balance between benefits and harms") required further development and clarification that were considered in the current version of the EtD framework. Conclusions The use of an EtD framework in guideline development offers a structured and explicit way to record and report the judgments and discussion of guideline panels during the formulation of recommendations. In addition, it facilitates the formulation of recommendations, assessment of their strength, and identifying gaps in research.